Genomic profiling proves metastasis of cutaneous melanoma to vitreal fluid. Issue 6 (December 2020) - Padrnos, Leslie J.; Houghton, Odette M.; Iacob, Codrin E.; Kurli, Madhavi; Ocal, Idris T.; Bryce, Alan H.
Abstract : Cutaneous melanoma metastases can contribute to visual disturbances through a variety of factors, including metastasis to the vitreal fluid. The optimum management of metastatic cutaneous melanoma to the vitreal fluid is unknown, but can include radiation therapy or systemic therapy including immunotherapy. A high degree of suspicion is necessary to consider this complication while working with patients with cutaneous melanoma.